Non-cash benefits and the distribution of economic welfare - Callan, Tim; Keane, Claire (Economic & Social Studies, 2009)
Non-cash benefits can have substantial effects on the distribution of economic welfare. Standard approaches to the inclusion of non-cash benefits in broader measures of resources have failed to take adequate account of the pattern of needs associated with the greater use of health and education services. Our results, for Ireland in the year 2000, show that it is possible to derive more appropriate measures of total resources than have been derived using standard methods. The results indicate that the greatest impact comes from the inclusion of imputed rent for owner occupation as part of the resource measure. When this is done, the rate of ?resource poverty? for older people is substantially reduced, in line with results which use indicators of standard of living as well as cash incomes (?consistent poverty?).
Paper delivered at the Twenty-Second Annual Conference of the Irish Economic Association, Westport, Co. Mayo, 25-27 April, 2008
Keywords: Non-cash benefits; Welfare distribution; Ireland; Poverty; Economic welfare